Effectiveness of Cognitive Behavioral Group Therapy for Treatment of Posttraumatic Stress Disorder: A Systematic Review - Seda Tokgunaydin; Serap Tekinsav Sutcu (Psikiyatride Güncel Yaklaşımlar, 2016)
This study aims to review empirical studies that were used to evaluate the effectiveness of cognitive-behavioral group therapy programs for the treatment for posttraumatic stress disorder. Articles in English and Turkish that were published between the years of 2000 and 2015 (February) have been searched in national and international databases. The articles that were gathered by the search have been read and the ones that were not therapy effectiveness studies, cognitive behavioral group therapies and that included posttraumatic stress disorder comorbid with alcohol/substance abuse, personality disorders and psychotic disorders were eliminated. The remaining 13 studies that fulfiilrf research criteria were introduced in the context of method and therapy characteristics. It can be seen that the cognitive behavioral group therapies are effective in decreasing the symptoms of posttraumatic stress disorder and/or comorbid disorders. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2016; 8(Supplement 1): 95-107]